Castor oil and mineral oil nanoemulsion: development and compatibility with a soft contact lens. (March 2014) - Katzer, Tatiele; Chaves, Paula; Bernardi, Andressa; Pohlmann, Adriana R.; Guterres, Silvia S.; Beck, Ruy C. R.
Abstract Context: The non-invasive ophthalmic therapy has a drawback: low residence time in the eye socket. Nanoparticles and contact lenses have been studied as promising ocular drug delivery systems. Objective: To develop a nanoemulsion and evaluate its compatibility with a soft contact lens as a potential strategy for ocular delivery. Materials and methods: The formulations were developed by spontaneous emulsification and fully characterized. Two drops of nanoemulsion were instilled on the surface of a commercial contact lens and its transparency was measured using a UV-Vis spectrophotometer. Before and after the instillation of the drops, the morphology (scanning electron microscopy – SEM) and ion permeability of the lenses were analyzed. Results: The formulations had a mean particle size of 234 nm, polydispersity below 0.16, zeta potential of −8.56 ± 3.49 mV, slightly acid pH, viscosity ≈1.2 mPa s−1 and spherical-shaped particles. Nanoemulsion was non-irritant (hen's egg test-chorioallantoic membrane), which was confirmed by the cytotoxicity studies in the SIRC cell cultures. After instillation, SEM analysis showed nanodroplets inside and on the surface of the lenses, although their transparency remained near 100%. No significant differences were found between lens ion permeability coefficients before and after instillation. Conclusions: Formulations presented appropriate physicochemical characteristics and suitability for ocular application. The contact lens remained transparent and ion-permeable after association with the formulation.